Real-time chlorophyll fluorescence monitoring reveals dynamic acclimation of lettuce to temperature and light stress in controlled environments - Nam, Suyun; Ferrarezi, Rhuanito Soranz (Frontiers in Plant Science, 2026)
Real-time monitoring of photosynthetic efficiency can improve our understanding of plant stress responses. In this study, we used a high-frequency chlorophyll fluorescence (CF) monitoring system to investigate the effects of combined temperature and light effects on lettuce. Plants were exposed to three temperatures (18, 25, and 32 °C) and two light intensities (150 and 500 μmol·m-2·s-1) for one week, and CF parameters were measured every 30 minutes. Gas exchange measurements were conducted at 2 and 7 days after treatment (DAT). High light combined with low temperature initially suppressed ΦPSII but gradually improved via reductions in quantum yield of non-regulated energy dissipation (ΦNO), indicating adjustments in the photosynthetic machinery. While the quantum yield of non-photochemical quenching (ΦNPQ) decreased sharply only on the first day, ΦNO continued to decline, highlighting its role in longer-term acclimation. In contrast, high temperatures enhanced CO2 assimilation through elevated stomatal conductance; however, the maximum efficiency of PSII (Fv/Fm) remained suppressed (~0.81), suggesting sustained photoinhibition. The relationship between electron transport rate (ETR) and photosynthetic rate (A) varied with temperature and time, indicating that the efficiency of converting photochemical energy into carbon assimilation depended on stress conditions and the acclimation stage. However, cumulative ETR integrated over the experiment period was significantly associated with shoot dry weight independent of temperature conditions, indicating that temporally integrated CF metrics retain predictive value for growth, unlike instantaneous CF parameters. These findings demonstrate that high-resolution CF monitoring captures subtle and dynamic photosynthetic responses that are not detectable via single-point gas exchange measurements alone. The ability to interpret changes in CF parameters in real-time provides valuable insights into plant acclimation and stress physiology for the optimization of environmental conditions in controlled environment agriculture systems.